De-layering of copper and low-k dielectrics for semiconductor devices failure analysis - Ng, Mei Zhen. (2010)
This project aims to quantify the rate of copper de-layered during Chemical Mechanical Polishing for semiconductor devices. This is to improve the effectiveness of de-layering copper during failure analysis since copper is prone to smearing, erosion and dishing. The report is generally divided into three parts. The first part begins with the description of the introduction and theoretical background of the types of techniques used in failure analysis, why copper is chosen over aluminum and the challenges faced when copper is used and failure analysis characterization.